Electrode and electrochemical device including same
By employing a primer layer with high binder and conductor content and a solvent-free drying process, the electrode manufacturing process achieves improved adhesion and reduced resistance, addressing uneven drying and adherence issues in lithium secondary batteries.
Patent Information
- Application Number
- JP2024539865
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-14
- Filing Date
- 2023-01-30
- Publication Date
- 2025-01-28
AI Technical Summary
The manufacturing process of lithium secondary batteries is prone to issues such as pinholes, cracks, and uneven drying of the electrode active layer, leading to reduced quality and adherence problems, particularly at the corners, which are exacerbated by the use of solvents that cause uneven drying and slurry flow before complete solidification.
The development of electrodes with a primer layer containing a binder and conductor, where the content of these components exceeds 90% of the total weight, eliminating the need for dispersants and ensuring uniform drying and adherence by using a method that involves spraying granules onto a collector and pressing them to form a layer without solvent evaporation.
This approach results in electrodes with enhanced adhesion and life characteristics, suitable for rapid charging with reduced resistance, and improves the overall quality and consistency of electrochemical elements.
Smart Images

Figure 2025502839000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode and an electrochemical device including the same. This application claims priority to Korean Patent Application No. 2022-0013755 filed on January 28, 2022 and Korean Patent Application No. 2022-0031453 filed on March 14, 2022, and the entire contents disclosed in the specification and drawings of said applications are incorporated herein by reference. [Background technology]
[0002] As the use of fossil fuels increases rapidly, the demand for alternative and clean energy is increasing, and as part of this, the field in which research is most active is the field of power generation and storage using electrochemistry. Currently, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and its range of use is expanding. Lithium secondary batteries, which are representative of such secondary batteries, are not only used as an energy source for mobile devices, but are also being used as a power source for electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution, and their range of use is expanding as an auxiliary power source for grid-based power generation.
[0003] The manufacturing process of such a lithium secondary battery is roughly divided into three steps: an electrode manufacturing process, an electrode assembly manufacturing process, and a chemical formation process. The electrode manufacturing process is further divided into an electrode mixture mixing process, an electrode coating process, a drying process, a rolling process, a slitting process, a winding process, etc. Among these, the electrode mixture mixing process is a process of blending components for forming an electrode active layer where an electrochemical reaction actually occurs in the electrode, and in detail, an electrode active material, which is an essential element of the electrode, and other additives such as a conductive material and a filler, a binder for binding between powder particles and adhesion with a current collector, and a solvent for viscosity imparting and dispersing powder are mixed to prepare a slurry having fluidity.
[0004] The composition mixed to form the electrode active layer may be broadly called an electrode mixture. Then, an electrode coating process is performed to coat the electrode mixture on an electrically conductive collector, and a drying process is performed to remove the solvent contained in the electrode mixture. The electrode is then rolled to a desired thickness.
[0005] Meanwhile, the evaporation of the solvent contained in the electrode mixture during the drying process may induce defects such as pinholes and cracks in the formed electrode active layer. In addition, the difference in the evaporation speed of the solvent may cause the powder to float due to the inside and outside of the active layer not being dried uniformly, i.e., the powder in the area that dries first may float up and form gaps with the area that dries later, resulting in a deterioration in the quality of the electrode.
[0006] In addition, when manufacturing an electrode by such a slurry coating process, the slurry may flow off before the drying of the slurry is completed, and the shape of the electrode may not completely match the original design shape. In particular, this phenomenon is more noticeable at the corners of the end of the electrode. That is, the slurry may flow off and the corners of the end of the electrode may be formed as inclined surfaces instead of right angles, or a coating surface may be formed in a part that should be maintained in a non-coated part beyond the boundary of the originally designed coating part. Meanwhile, an insulating part may be disposed to improve the insulation of the electrode. In a method for manufacturing an electrode by a slurry coating process, when a process of coating an insulating part on a non-coated part is performed after forming an electrode active material layer, the coating of the insulating part and the inclined surface of the electrode active material layer may overlap. When manufacturing an electrode by the electrode slurry coating method, an inclined surface is formed at the end of the electrode active material layer, and when an insulating layer is coated on an electrode having an electrode active material layer with such an inclined surface, the inclined surface of the electrode active material layer and the insulating layer overlap. Therefore, further process management is required to minimize the overlap width.
[0007] In order to solve the above problems, a drying device capable of adjusting the evaporation rate of the solvent while drying the inside and outside of the active layer uniformly has been considered, but such a drying device is very expensive and requires considerable cost and time to operate, which is disadvantageous in terms of manufacturing process. Therefore, research into manufacturing dry electrodes that do not use solvents has been actively conducted recently. Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide an electrode, particularly a dry electrode, having excellent qualities such as life characteristics and adhesive strength, and an electrochemical device including the same. [Means for solving the problem]
[0009] In order to achieve the above object, according to one aspect of the present invention, there is provided an electrode according to the following embodiment.
[0010] According to the first embodiment, Provided is an electrode comprising: a current collector; a primer layer formed on at least one surface of the current collector; and an electrode active material layer formed on the current collector having the primer layer, wherein the electrode active material layer comprises an electrode active material and an electrode binder, the electrode active material comprising a plurality of granules bound by the electrode binder, the primer layer comprises a binder and a conductive material, and the sum of the contents of the binder and the conductive material in the primer layer is 90 wt % or more.
[0011] According to the second embodiment, in the first embodiment, The sum of the content of the binder and the conductive material may be 94 wt % or more based on the total weight of the primer layer.
[0012] According to the third embodiment, in the first or second embodiment, The primer layer may be substantially free of a dispersant.
[0013] According to a fourth embodiment, in any one of the first to third embodiments, When the primer layer further includes a dispersant, the content of the dispersant may be 6 wt % or less based on the total weight of the primer layer.
[0014] According to the fifth embodiment, in the third or fourth embodiment, The dispersant may be a cellulose-based polymer, an emulsifying surfactant, or two or more thereof.
[0015] According to the sixth embodiment, in any one of the first to fifth embodiments, The binder may have a glass transition temperature Tg of -40°C to 45°C.
[0016] According to the seventh embodiment, in any one of the first to sixth embodiments, The binder may be any of styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), styrene butadiene styrene block polymer (SBS), styrene ethylene butadiene block polymer (SEB), styrene-(styrene butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), ethylene-propylene-diene terpolymer (EPDM), poly(ethylene-co-propylene-co-5-methylene-2-norbornene), polytetrafluoroethylene (PTFE), polyvinylidene fluoride, polyvinyl chloride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, and the like. The polymerizable compound may include, for example, fluoride-co-trichloroethylene, polymethylmethacrylate, polyethylhexyl acrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene, polypropylene, ethylene-vinyl acetate, polyethylene oxide, polypropylene oxide, polyarylate, cyanoethylpullulan, cyanoethylpolyvinylalcohol, or two or more of these.
[0017] According to the eighth embodiment, in any one of the first to seventh embodiments, The electrode active material layer may include a plurality of granules including an electrode active material, an electrode conductive material, and an electrode binder, in which the electrode active material and the electrode conductive material are bound by the electrode binder.
[0018] According to the ninth embodiment, in any one of the first to eighth embodiments, The electrode conductive material is 10 m 2 / g~1,400m 2 The specific surface area may be 100 / g.
[0019] According to a tenth embodiment, in any one of the first to ninth embodiments, The thickness of the primer layer may be from 300 nm to 1.5 μm.
[0020] According to the eleventh embodiment, in any one of the first to eleventh embodiments, The granules included in the electrode active material layer may be prepared by a method including the steps of: mixing an electrode active material and an electrode binder with a dispersion medium to prepare a slurry; and spray-drying the slurry.
[0021] According to the twelfth embodiment, in the eleventh embodiment, The slurry may further include an electrode conductive material.
[0022] According to the thirteenth embodiment, in any one of the first to twelfth embodiments, The electrode may be manufactured by a method including the steps of: dispersing a plurality of granules on a current collector; and rolling the dispersed plurality of granules to form an electrode active material layer. According to another aspect of the present invention, there is provided an electrochemical device according to the following embodiment. According to the fourteenth embodiment, An electrochemical device is provided, in which an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode is housed in a battery case together with a lithium-containing non-aqueous electrolyte, and at least one of the positive electrode and the negative electrode is an electrode according to any one of the first to thirteenth embodiments. Effect of the Invention
[0023] According to an embodiment of the present invention, an electrode having excellent qualities such as life characteristics and adhesive strength, particularly suitable for a dry electrode, is provided.
[0024] In addition, according to an embodiment of the present invention, there is provided an electrochemical device that has low resistance characteristics, improved life characteristics, and is applicable to rapid charging.
[0025] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. The present invention should not be interpreted as being limited only to the matters described in the drawings. [Brief description of the drawings]
[0026] [Figure 1] 1 is a schematic diagram showing the surface and interior of a granular particle according to one embodiment of the present invention. [Figure 2a] 1 is a cross-sectional SEM image of an electrode before rolling in Example 1 according to an embodiment of the present invention. [Figure 2b] 1 is a cross-sectional SEM image of an electrode before rolling in Example 2 according to an embodiment of the present invention. [Diagram 3] 1 is a cross-sectional image of the granular particles produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The present invention will be described in detail below. However, the present invention is not limited to the following content, and each component may be modified in various ways or mixed selectively as necessary. Therefore, it should be understood that all modifications, equivalents, or alternatives included in the spirit and technical scope of the present invention are incorporated.
[0028] Throughout the specification, when a part "comprises" a certain element, it does not mean excluding other elements, but means that the part may further include other elements, unless otherwise specified.
[0029] The terms "about," "substantially," and the like, used throughout this specification, when given the meaning given, are used to mean a numerical value or a approximation thereof, given the inherent manufacturing and material tolerances, and are used to prevent unconscionable infringers from unfairly using disclosures in which precise or absolute numerical values are recited to aid in the understanding of this application.
[0030] Throughout this specification, the phrase "A and / or B" means "A or B, or all of these."
[0031] Certain terminology used herein is for convenience and is not limiting. Terms such as "top," "bottom," "left," "right," "front," "rear," "inside," and "outside" are used to describe relative positions and orientations of components relative to one another, rather than absolute positions, or may indicate positions and orientations in the drawings to which reference is made. The above terms include other words containing these terms, derivatives thereof, and words of similar meaning.
[0032] The term "glass transition temperature Tg" used herein may be measured by a conventional method known in the art, for example, by differential scanning calorimetry (DSC). For example, the measurement of glass transition temperature by differential scanning calorimetry may be performed by measuring the amount of heat while changing the temperature in the range of -80°C to 300°C using a Discovery DSC 250 instrument from TA Instruments. Specifically, the temperature of the sample to be measured may be changed from 25°C (start) -> 250°C (first heating) -> -80°C (first cooling) -> 300°C at a rate of 10°C / min in the order of first heating -> first cooling -> second heating. In this case, the first heating process is for evaporating moisture remaining in the sample, and the first cooling and second heating processes may be for analyzing thermal behavior from a heat thermogram.
[0033] In the present specification, the term "porosity" refers to the ratio of the volume of pores to the total volume of a structure, and may be used interchangeably with terms such as porosity and porosity, with the unit being %. In the present invention, the measurement of the porosity is not particularly limited, and in one embodiment of the present invention, for example, the measurement may be performed by a BET (Brunauer-Emmett-Teller) measurement method using nitrogen gas or a mercury penetration method (Hg porosimeter) and ASTM D-2873. Alternatively, the true density of the separator may be calculated from the density (apparent density) of the separator, the composition ratio of the materials contained in the separator, and the density of each component, and the porosity of the separator may be calculated from the difference between the apparent density and the true density (net density).
[0034] The term "average particle size D50" used in the specification means the particle size at 50% of the cumulative particle number distribution by particle size, and the particle size may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the diffraction pattern difference according to particle size when the particles pass through a laser beam. The D50 particle size can be measured by calculating the particle diameter at the 50% point of the cumulative particle number distribution by particle size in the measuring device.
[0035] The "thickness" of each layer included in the electrode used in this specification may refer to a value measured by a known method for measuring thickness. The method for measuring thickness is not limited thereto, but may be, for example, a value measured using a thickness meter (Mitutoyo, VL-50S-B).
[0036] The "specific surface area" used in the present specification may be a value measured by a known method for measuring a specific surface area. The method for measuring the specific surface area is not limited thereto, and may be, for example, a value measured by a flow method or a stationary method.
[0037] The present invention relates to an electrode and an electrochemical device including the electrode. The electrochemical device of the present invention includes all devices that perform electrochemical reactions, and specifically includes all types of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitors. In the present invention, the electrochemical device is preferably a secondary battery, and more preferably a lithium ion secondary battery.
[0038] According to one aspect of the invention, an electrode comprises: An electrode including a current collector, a primer layer formed on at least one surface of the current collector, or a part of the entire surface of the current collector, and an electrode active material layer formed on the current collector having the primer layer, wherein the electrode active material layer includes an electrode active material and an electrode binder, and the electrode active material includes a plurality of granules bound by the electrode binder, and the primer layer includes a binder and a conductive material, and a sum of the contents of the binder and the conductive material in the primer layer may be 90 wt % or more.
[0039] An electrode according to one aspect of the present invention includes an electrode active material layer including the granules, and in this case, a primer layer including a binder and a conductive material, the sum of the contents of the binder and the conductive material being 90 wt % or more based on the total weight of the primer layer, ensures stability over time of the primer layer, and thus exhibits excellent physical properties such as adhesive strength and life characteristics, but the present invention is not limited thereto.
[0040] First, the primer layer will be described in detail. According to one embodiment of the present invention, the sum of the content of the binder and the conductive material based on the total weight of the primer layer may be specifically 91 weight % or more, 92 weight % or more, 93 weight % or more, 94 weight % or more, 95 weight % or more, 96 weight % or more, 97 weight % or more, 98 weight % or more, 99 weight % or more, 100 weight % or less, 99 weight % or less, 98 weight % or less, 95 weight % or less, or 93 weight % or less.
[0041] According to one embodiment of the present invention, the primer layer includes a binder and a conductive material, and may further include a dispersant.
[0042] According to another embodiment of the present invention, the primer layer includes a binder and a conductive material, but may be substantially free of a dispersant.
[0043] In this specification, the term "substantially free" means not only that the component is not contained at all, but also that the component is contained in such a small amount that the function of the component is not realized. For example, the content of the component that is not substantially contained may be 6 wt% or less, 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, 1 wt% or less, 0.5 wt% or less, or 0 wt% (i.e., not contained at all).
[0044] Therefore, the primer layer "substantially does not contain a dispersant" means not only that the primer layer does not contain any dispersant at all, but also that even if the primer layer contains a dispersant, the dispersant is contained in such a small amount that the function of the dispersant, i.e., the function of dispersing the binder and the conductive material, is not realized. For example, when the primer layer contains a dispersant, the content of the dispersant based on the total weight of the primer layer may be 6 wt% or less, 5 wt% or less, 4 wt% or less, 3 wt% or less, 2 wt% or less, 1 wt% or less, 0.5 wt% or less, or 0 wt% (i.e., not contained at all).
[0045] According to one embodiment of the present invention, the substantially free dispersant may be decomposed when exposed to the atmosphere, causing deterioration of the primer layer over time.
[0046] The dispersant may include, but is not limited to, a cellulose-based polymer, an emulsifying surfactant, or two or more of these.
[0047] Examples of the cellulose-based polymer include, but are not limited to, carboxymethyl cellulose (CMC), alkali metal salts of carboxymethyl cellulose, hydroxymethyl cellulose (HMC), alkali metal salts of hydroxymethyl cellulose, hydroxyethyl cellulose (HEC), alkali metal salts of hydroxyethyl cellulose, hydroxypropyl cellulose (HPC), alkali metal salts of hydroxypropyl cellulose, ethyl hydroxyethyl cellulose (EHEC), methyl hydroxymethyl cellulose (MHMC), methyl hydroxyethyl cellulose (MHEC), ethyl hydroxymethyl cellulose (EHMC), methyl cellulose (MC), ethyl cellulose (EC), hydroxypropyl methyl cellulose (HPMC), hydroxyethyl methyl cellulose (HEMC), or mixtures of two or more of these.
[0048] The emulsifying surfactant may be, for example, a nonionic surfactant, an anionic surfactant, an amphoteric surfactant, or a mixture of two or more thereof, but is not limited thereto. The nonionic surfactant may be, for example, an ethoxylate, an amidoethoxylate, an amine oxide, an alkylglucoside, or a mixture of two or more thereof, but is not limited thereto. The anionic surfactant may be, for example, a phosphate ester, an isothionate, a sulfate, a sulfonate, a taurate, or a mixture of two or more thereof, but is not limited thereto. The amphoteric surfactant may be, for example, a betaine, a glycinate, an alkylamidoalkylamine, or a mixture of two or more thereof, but is not limited thereto.
[0049] According to another embodiment of the present invention, the primer layer may be substantially free of a cellulosic polymer as a dispersant.
[0050] According to yet another embodiment of the present invention, the primer layer may be substantially free of carboxymethyl cellulose, hydroxypropyl methyl cellulose or a mixture thereof as a dispersant.
[0051] According to yet another embodiment of the present invention, the primer layer may be substantially free of emulsifying surfactants.
[0052] According to one embodiment of the present invention, the binder can be any known binder used for a primer layer without any particular limitation.
[0053] According to another embodiment of the present invention, it is preferable to use a binder that can ensure the stability of the primer layer over time. Specifically, the binder may have a glass transition temperature Tg of 45° C. or less. More specifically, the glass transition temperature of the binder may be −40° C. to 45° C. The glass transition temperature of the binder may be, for example, −35° C. to 45° C., −30° C. to 40° C., −25° C. to 35° C., −20° C. to 30° C., or −15° C. to 25° C.
[0054] According to yet another embodiment of the present invention, the binder is, for example, styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), styrene butadiene styrene block polymer (SBS), styrene ethylene butadiene block polymer (SEB), styrene-(styrene butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), ethylene-propylene-diene terpolymer (EPDM), poly(ethylene-co-propylene-co-5-methylene-2-norbornene), polytetrafluoroethylene (PTFE), polyvinylidene fluoride, polyvinyl chloride, polyvinylidene fluoride-hexafluoropropylene ... The polymer may include polyvinyl fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyethylene, polypropylene, ethylene-vinyl acetate, polyethylene oxide, polypropylene oxide, polyarylate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, or two or more thereof.Specifically, the binder may include styrene butadiene rubber (SBR), nitrile butadiene rubber (NBR), polymethylmethacrylate, polyethylhexylacrylate, polybutylacrylate, or two or more thereof.
[0055] According to yet another embodiment of the present invention, the binder has the above-mentioned glass transition temperature value and can be one or a mixture of two or more selected from the above-mentioned types.
[0056] According to yet another embodiment of the present invention, the binder may be a styrene butadiene rubber (SBR) having a glass transition temperature Tg of -40°C to 45°C, a nitrile butadiene rubber (NBR) having a glass transition temperature Tg of -40°C to 45°C, or a mixture thereof.
[0057] According to one embodiment of the present invention, the conductive material is 10 2 / g~1,400m 2 For example, the conductive material may have a specific surface area of 10 m 2 / g~400m 2 / g or 30m 2 / g~1,400m 2 / g.
[0058] According to another embodiment of the present invention, the conductive material has a specific surface area of 30 m 2 / g~1,400m 2 / g and may be spherical. In this case, the size of the primary particles of the spherical conductive material may be, for example, 10 nm to 100 nm, specifically 15 nm to 70 nm, but is not limited thereto.
[0059] According to yet another embodiment of the present invention, the conductive material has a specific surface area of 10 m 2 / g~400m 2In this case, the diameter of the cross section of the tubular conductive material in the direction perpendicular to the longitudinal direction may be 0.1 nm to 3 nm, specifically 0.3 nm to 1.5 nm, but is not limited thereto.
[0060] The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black-based carbon compounds such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used. More specifically, in order to uniformly mix the conductive material and improve conductivity, activated carbon, graphite, carbon black, carbon nanotubes, or a mixture of two or more of these may be included, and more specifically, activated carbon may be included.
[0061] According to one embodiment of the present invention, the primer layer contains the above-mentioned composition and has a thickness of 300 nm to 1.5 μm, specifically 700 nm to 1.3 μm, but is not limited thereto.
[0062] Next, the current collector contained in the electrode and the electrode active material layer containing granules will be described.
[0063] According to one embodiment of the present invention, the current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. The current collector may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. The current collector may also be formed with fine irregularities on its surface to increase the adhesive strength of the active material, and may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. Meanwhile, in one embodiment of the present invention, the current collector may have a thickness of 10 μm to 25 μm, but is not particularly limited thereto. The current collector may have a thickness of, for example, 10 μm to 20 μm.
[0064] The granules included in the electrode active material layer include an active material and a binder. The granules may be composite particles including the active material and the binder.
[0065] According to one embodiment of the present invention, the granules may have the form of composite particles containing an active material, a binder, and any optional components added as necessary. In one embodiment of the present invention, the granules may be formed by granulating two or more active material particles bound together by the binder, and then forming them into secondary particles.
[0066] In this specification, components contained in the electrode active material layer may be referred to as "electrode active material," "electrode conductive material," and "electrode binder" to distinguish them from components contained in the primer layer.
[0067] The electrode active material means an aggregate of particles, and the diameter of each particle of the electrode active material may be, for example, 0.05 μm to 2 μm. In one embodiment of the present invention, the content of the electrode active material may be, for example, 80 wt% or more or 90 wt% or more, and the content of the electrode binder may be, for example, 20 wt% or less or 10 wt% or less, based on the total weight of the granule. In one embodiment of the present invention, the granule may further include an electrode conductive material as an optional component, if necessary. When the electrode conductive material is included, the content of the electrode conductive material may be in the range of 0.1 wt% to 20 wt% or less, preferably 0.1 wt% to 10 wt%, more preferably 0.1 wt% to 5 wt%, based on the total weight of the granule.
[0068] According to one embodiment of the present invention, the content of the electrode active material may be 85wt% to 98wt% based on the total weight of the granule. Within this range, the content of the electrode binder may be 0.5wt% to 10wt%, and the content of the electrode conductive material may be 0.5wt% to 5wt%. According to yet another embodiment, the content of the electrode active material may be 90wt% to 98wt%, the content of the electrode binder may be 0.5wt% to 5wt%, and the content of the electrode conductive material may be 0.5wt% to 5wt%.
[0069] In the present invention, the granule has a greater amount of electrode binder contained in a surface portion 102 of the granule than in a center portion 101 of the granule. The amount of binder may refer to weight or volume.
[0070] In addition, or independently, the granule may have a content (wt%) B of the electrode binder contained in the center 101 of the granule relative to the total weight 100 wt%. c / G t The content (wt%) of the electrode binder contained in the surface portion 102 of the granule B s / G t Here, the B c is the weight of the binder contained in the core, and B s is the weight of the binder contained in the surface area, and G tmeans the total weight of the granules.
[0071] In addition, or independently, the granule may have a content (vol%) B of the electrode binder contained in the center 101 of the granule relative to 100 vol% of the total volume. c / G t The content of the electrode binder contained in the surface portion 102 of the granule is vol% B s / G t Here, the B c is the volume of the binder contained in the core, and B s is the volume of the binder contained in the surface area, and G t means the total volume of the granule particles.
[0072] Here, the surface portion means a region near the surface of the granule from the surface of the granule to a predetermined depth toward the center of the granule, and the central portion means a portion other than the surface portion. In one embodiment of the present invention, the surface portion may mean a region from the center of the granule to the outside of the granule, up to 70% or more of the granule surface in the radius direction. In one embodiment of the present invention, the surface portion may mean, for example, a region up to 80% or more, 85% or more, 90% or more, or 95% or more of the granule surface in the radius direction.
[0073] In one embodiment of the present invention, the centre of the granule may refer to the ½ point of the longest diameter of the granule.
[0074] In one embodiment of the present invention, in a region from the center of the granule to the surface of the granule at 90% or more of the radius, the content of the electrode binder relative to the total weight of the granule in that region may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.
[0075] In yet another embodiment of the present invention, in a region from the center of the granule to the surface of the granule at 95% or more of the radius, the content of the electrode binder relative to the total weight of the granule in that region may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.
[0076] In yet another embodiment of the present invention, in a region from the center of the granule to 99% or more of the granule surface in a radius thereof, the content of the electrode binder relative to the total weight of the granule in said region may be 50 wt% or more, 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more.
[0077] In one embodiment of the present invention, in a region from the center of the granule to the surface of the granule at 90% or more of the radius, the content of the electrode binder relative to the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.
[0078] In yet another embodiment of the present invention, in a region from the center of the granule to the surface of the granule at 95% or more of the radius, the content of the electrode binder relative to the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.
[0079] In yet another embodiment of the present invention, in a region from the center of the granule to 99% or more of the surface of the granule at a radius, the content of the electrode binder relative to the total volume of the granule in that region may be 50 vol% or more, 60 vol% or more, 70 vol% or more, 80 vol% or more, or 90 vol% or more.
[0080] 1 is a schematic SEM image of a granular particle according to an embodiment of the present invention. Referring to FIG 1, the granule can be divided into a surface region 102 having a high binder content from the surface to a predetermined depth toward the center of the particle, and a central portion (core portion) 101 surrounded by the surface portion.
[0081] To describe the granule in more detail, the granule may have a central portion including a plurality of electrode active materials, and a surface portion including an electrode binder located on the entire or part of the outside of the central portion and binding the electrode active materials. That is, in the central portion of the granule, the plurality of electrode active materials are in surface contact, line contact, point contact, or contact with two or more of these to form an aggregate, and in the surface portion of the granule, an electrode binder is located on a portion or the entire outside of such an aggregate, and the electrode binder included in the surface portion may fix and bind the plurality of electrode active materials in the central portion of the granule to each other.
[0082] According to an embodiment of the present invention, a small amount of electrode binder may be further included in the center of the granule to connect and fix a plurality of electrode active materials to each other in the center of the granule. However, as described above, it is preferable that the content of the electrode binder is higher in the surface portion than in the center.
[0083] Meanwhile, in one embodiment of the present invention, the granule may have an aspect ratio of 0.5 to 1.0, preferably 0.75 to 1.0. The aspect ratio may mean the ratio between the length of the short axis and the length of the long axis of the granule. In yet another embodiment of the present invention, the average aspect ratio of the granule may have a value of, for example, 0.5 to 1.0, preferably 0.75 to 1.0, in which case, the average aspect ratio may mean the ratio between the average length of shortening and the average length of the long axis of the granule particles. In this case, the average length of shortening refers to the average value of the length in the axial direction having the shortest length of the granule, and the average length of the long axis refers to the average value of the length in the axial direction having the longest length of the granule. When the aspect ratio of the granule satisfies such a range, it is advantageous in terms of having sufficient fluidity suitable for the process.
[0084] Meanwhile, in one embodiment of the present invention, the particle size may be in the range of 0.1 μm to 1,000 μm based on the longest diameter of the granule. In another embodiment of the present invention, the average particle size D50 of the granule may be in the range of 0.1 μm to 1,000 μm.
[0085] The conductive material (also referred to as "electrode conductive material") that may be contained in the granules is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. The description of the conductive material contained in the primer layer as the electrode conductive material is incorporated herein by reference. Meanwhile, in one embodiment of the present invention, the granular particles may contain only a single conductive material, or may contain two or more different conductive materials within one particle. For example, the granules may be a mixture of carbon black and carbon nanotubes in a predetermined ratio as conductive materials.
[0086] The binder contained in the granules (also referred to as "electrode binder") is not particularly limited as long as it does not induce chemical changes in the battery and uniformly disperses the powdered active material and conductive material. The description of the binder contained in the primer layer may be used for the electrode binder. Specifically, it is desirable to use an aqueous binder as the electrode binder among the binders contained in the primer layer.
[0087] According to one embodiment of the present invention, the electrode binder may include, for example, a diene-based polymer, an acrylate-based polymer, a fluorine-based polymer, a styrene-based polymer, or two or more of these.
[0088] Examples of the diene polymer include polymers containing monomer units derived from conjugated dienes such as butadiene and isoprene, and the ratio of the monomer units may be usually 40 wt% or more, preferably 50 wt% or more, and more preferably 60 wt% or more. Specific examples include conjugated diene homopolymers such as polybutadiene or polyisoprene, aromatic vinyl-conjugated diene copolymers such as styrene-butadiene copolymer (SBR) which may be carboxy-modified, cyanide vinyl conjugated diene copolymers such as acrylonitrile-butadiene copolymer (NBR), hydrogenated SBR, hydrogenated NBR, etc.
[0089] Examples of the acrylate polymer include polymers containing monomer units derived from acrylic acid esters and / or methacrylic acid esters. The proportion of monomer units derived from acrylic acid esters and / or methacrylic acid esters in the acrylate polymer is usually 40 wt% or more, preferably 50 wt% or more, and more preferably 60 wt% or more. Specific examples of acrylate polymers include crosslinked acrylate polymers such as 2-ethylhexyl acrylate-methacrylic acid-acrylonitrile-ethylene glycol dimethacrylate copolymer, 2-ethylhexyl acrylate-methacrylic acid-methacrylonitrile-ethylene glycol dimethacrylate copolymer, 2-ethylhexyl acrylate-styrene-methacrylic acid-ethylene glycol dimethacrylate copolymer, butyl acrylate-acrylonitrile-diethylene glycol dimethacrylate copolymer, and butyl acrylate-acrylic acid-trimethylolpropane trimethacrylate copolymer; copolymers of ethylene and (meth)acrylic acid ester such as ethylene-methyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-ethyl methacrylate copolymer; polymers obtained by grafting a radical polymerizable monomer onto the copolymer of ethylene and (meth)acrylic acid ester; and the like. Examples of radical polymerizable monomers used in the graft polymers include methyl methacrylate, acrylonitrile, and methacrylic acid. In addition, copolymers of ethylene and (meth)acrylic acid, such as ethylene-acrylic acid copolymer and ethylene-methacrylic acid copolymer, can be used as the dispersion type binder.
[0090] The fluoropolymer may include polytetrafluoroethylene (PTFE), polyolefin, or a mixture thereof. In particular, the fluoropolymer may include polytetrafluoroethylene (PTFE), and more particularly, may be polytetrafluoroethylene (PTFE).
[0091] Specifically, the polytetrafluoroethylene (PTFE) may be contained in an amount of 60 wt % or more based on the total weight of the binder.
[0092] Meanwhile, the electrode binder may further include polyethylene oxide (PEO), polyvinylidene fluoride (PVdF), and polyvinylidene fluoride-co-hexafluoropropylene (PVdF-HFP).
[0093] Among these, from the viewpoints of obtaining an electrode active material layer having excellent adhesion to the current collector and surface smoothness, and of producing an electrode for an electrochemical element having high capacitance and low internal resistance, diene-based polymers and crosslinked acrylate-based polymers are preferred, and crosslinked acrylate-based polymers are particularly preferred.
[0094] The shape of the electrode binder is not particularly limited, but it is desirable that the electrode binder is granular because it has good binding properties and can suppress the decrease in the capacitance of the electrode produced and the deterioration due to repeated charging and discharging. Examples of granular electrode binders include those in which dispersed binder particles are dispersed in water, such as latex, and those in the form of powder obtained by drying such a dispersion. Such granular binders can be desirably included in the negative electrode.
[0095] Meanwhile, in one embodiment of the present invention, the granular particles may contain a single binder material or two or more different binder materials within one particle. For example, the granules may be a mixture of styrene butadiene rubber (SBR) and an acrylate polymer in a predetermined ratio as binder materials.
[0096] The electrodes according to the present invention can be positive or negative electrodes. In one embodiment of the present invention, when the electrode is used as a positive electrode, the electrode active material may be a positive electrode active material. The positive electrode active material may include, but is not limited to, lithium transition metal oxides; lithium metal iron phosphate; lithium nickel-manganese-cobalt oxide; an oxide in which a part of lithium nickel-manganese-cobalt oxide is substituted with another transition metal; or two or more of these. Specifically, the positive electrode active material may include, but is not limited to, layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or compounds substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); 2-x M x Lithium manganese composite oxides represented by Li2Mn3MO8 (where M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1) or Li2Mn3MO8 (where M=Fe, Co, Ni, Cu or Zn); Li in which part of the Li in the chemical formula is replaced by an aluminum ion. 1+x (NiaCobMncAld) 1-x O2 (x=0-0.03, a=0.3-0.95, b=0.01-0.35, c=0.01-0.5, d=0.001-0.03, a+b+c+d=1); lithium metal phosphate LiMPO4 (where M=Fe, CO, Ni or Mn), disulfide compounds; Fe2(MoO4)3, and the like, but are not limited to these.
[0097] In other embodiments of the present invention, when the electrode is used as a negative electrode, the electrode active material can be a negative electrode active material. The negative electrode active material can be, for example, carbon such as graphitized carbon, natural graphite or artificial graphite; Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0<x≦1; 1≦y≦3; 1≦z≦8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; silicon-based oxides such as SiO, SiO / C, SiO2; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials, etc. can be used, but are not limited thereto.
[0098] According to one embodiment of the present invention, the granule may contain a single electrode active material in one particle or two or more different electrode active materials. The electrode active material is not particularly limited as long as it is the above-described component. For example, the granule may contain artificial graphite and natural graphite as the electrode active material, and the artificial graphite and natural graphite may be mixed in a predetermined ratio.
[0099] According to one embodiment of the present invention, the content of the electrode active material in the electrode active material layer is 85 to 98 parts by weight, and the content of the electrode binder can be 0.5 to 10 parts by weight. The content of the electrode active material is 90 to 98 parts by weight, and the content of the electrode binder can be 0.5 to 5 parts by weight.
[0100] According to one embodiment of the present invention, the electrode active material, electrode conductive material and electrode binder in the electrode active material layer may be mixed in a weight ratio of 80 to 99 parts by weight:0.5 to 10 parts by weight:0.5 to 10 parts by weight of the electrode active material:electrode conductive material:electrode binder, or in a weight ratio of 90 to 99 parts by weight:0.5 to 5 parts by weight:0.5 to 10 parts by weight of the electrode active material:electrode conductive material:electrode binder.
[0101] In one embodiment of the present invention, the electrode active material layer has a uniform distribution of the binder in the thickness direction. In a specific embodiment, the electrode active material layer may have a difference of 10 wt% or less between the binder content (wt%) in the upper 100 wt% and the binder content (wt%) in the lower 100 wt% in the upper and lower parts of the electrode active material layer, which are divided based on a point 50% from the current collector in the thickness of the electrode active material layer. In addition, the difference of 10 wt% or less between the binder content in a region up to 15% of the thickness from the current collector toward the electrode surface layer and the binder content in a region up to 15% of the thickness from the surface layer of the electrode active material layer toward the current collector may be.
[0102] Such a distribution of the binder may be due to the fact that the electrode active material layer according to the present invention is manufactured by compressing the granules. As described below, the method for manufacturing an electrode according to the present invention is characterized in that after manufacturing granular particles containing an electrode material, the granular particles are spread on a current collector or the like and compressed so that the granules are accumulated in a layered structure. In the case of a method for manufacturing an electrode involving the manufacture of a slurry, the migration of the binder is induced by the evaporation of the solvent when the slurry is dried, and the binder is distributed intensively on the surface of the electrode. However, in the present invention, since a method of compressing and accumulating dry granules without using a solvent is applied, the migration phenomenon of the binder does not occur. Therefore, the binder is uniformly distributed in the thickness direction in each unit layer. The electrode active material layer includes an electrode active material and an electrode binder. In the present invention, the electrode active material layer may have a form in which the granules are compressed and accumulated in a layered structure. When the granules are introduced into an electrode, the aspect ratio or particle size range of the granules may not be maintained in the initial state due to a calendaring process described below. The electrode active material layer may include 80 wt% or more, 90 wt% or more, 95 wt% or more, or 99 wt% or more of the granules relative to 100 wt% of the electrode active material layer.
[0103] In one embodiment of the present invention, the electrode active material layer may further include an electrode active material, an electrode binder, an electrode conductive material, etc., which are not contained in the granules but are free from the granules, or may further include granule particles having an aspect ratio and / or a particle size range outside the above-mentioned ranges.
[0104] In some cases, the electrode active material layer may further contain a filler, which is a component that suppresses the expansion of the electrode active material layer, and the filler is not particularly limited as long as it does not induce chemical changes in the battery and is a fibrous material. For example, olefin polymers such as polyethylene and polypropylene, and fibrous materials such as glass fiber and carbon fiber are used.
[0105] The electrode active material layer is a layered structure of the granules, and has pores provided by interstitial volumes between the granules, and exhibits porous properties derived from such a structure. In one embodiment of the present invention, the electrode active material layer preferably has a porosity of 20 vol% to 40 vol% in consideration of electrolyte impregnation, morphological stability, ion conductivity, and the like.
[0106] According to one embodiment of the present invention, the thickness of the electrode active material layer may be, for example, 30 μm to 300 μm, but is not limited thereto.
[0107] According to an embodiment of the present invention, the electrode active material layer may be formed as a single layer including one unit active material layer.
[0108] According to another embodiment of the present invention, the electrode active material layer may include a laminate in which two or more unit active material layers are laminated, and in this case, the active material, the conductive material, and the binder contained in each unit active material layer may be the same or different for each layer, but are not limited thereto.
[0109] According to one embodiment of the present invention, the granules included in the electrode active material layer may be prepared by a method including the steps of mixing an electrode active material and an electrode binder with a dispersion medium to prepare a slurry, and spray-drying the slurry.
[0110] According to one embodiment of the present invention, the granules included in the electrode active material layer may be prepared by a method including the steps of mixing an electrode active material, an electrode conductive material, and an electrode binder with a dispersion medium to prepare a slurry, and spray-drying the slurry.
[0111] First, the electrode active material, the electrode binder, and optionally the electrode conductive material and / or additional additives are dispersed or dissolved in a dispersion medium (a solvent for the electrode binder) to obtain a slurry in which the electrode active material, the electrode binder, and optionally the electrode conductive material and / or other additives are dispersed or dissolved.
[0112] The dispersion medium used to obtain the slurry is most preferably water, but an organic solvent may be used. Examples of organic solvents include alkyl alcohols such as methyl alcohol, ethyl alcohol, and propyl alcohol; alkyl ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran, dioxane, and diglyme; amides such as diethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone (hereinafter also referred to as NMP), and dimethylimidazolidinone; sulfur-based solvents such as dimethyl sulfoxide and sulfolane; and the like, with alcohols being preferred. The combined use of an organic solvent with a boiling point lower than that of water can increase the drying speed during fluidized granulation. In addition, the dispersibility or solubility of the negative electrode binder can change, so that the viscosity and fluidity of the slurry can be adjusted according to the amount or type of the dispersion medium, thereby improving production efficiency.
[0113] The amount of dispersion medium used when preparing the slurry may be an amount such that the solids concentration of the slurry is usually in the range of 1 wt% to 50 wt%, or 5 wt% to 50 wt%, or 10 wt% to 30 wt%.
[0114] The method or order of dispersing or dissolving the electrode active material, electrode binder, etc. in the dispersion medium is not particularly limited, and examples thereof include a method of adding the electrode active material and electrode binder to the dispersion medium and mixing them, a method of dissolving or dispersing the electrode binder in the dispersion medium and finally adding the electrode active material and mixing them, etc. In addition, as described above, a negative electrode conductive material, other additives, etc. may be selectively added to the dispersion medium. Therefore, examples of the method include a method of adding the electrode active material, electrode conductive material, and electrode binder to the dispersion medium and mixing them, a method of dissolving or dispersing the electrode binder in the dispersion medium and finally adding the electrode active material and electrode conductive material and mixing them, etc.
[0115] Examples of mixing means include mixing equipment such as a ball mill, a sand mill, a bead mill, a pigment disperser, a stone mill, an ultrasonic disperser, a homogenizer, a planetary mixer, etc. Mixing can be carried out, for example, at a temperature range of room temperature to 80° C. for 10 minutes to several hours.
[0116] Next, the slurry is spray-dried. The spray drying method is a method of spraying the slurry into hot air and drying it. Examples of the spraying method of the device used in the spray drying method include a rotating disk method and a nozzle pressurization method. The rotating disk method is a method in which the slurry is introduced almost at the center of a disk rotating at high speed, and when the slurry comes off the disk due to the centrifugal force of the disk, it is atomized and dried. The rotation speed of the disk depends on the size of the disk, but is usually 5,000 rpm to 35,000 rpm, preferably 15,000 rpm to 30,000 rpm. On the other hand, the nozzle pressurization method is a method in which the slurry is passed through a thin nozzle, and a high-pressure fluid such as air or other liquid is sprayed together with the slurry to spray it into a mist and dry it.
[0117] In one embodiment of the present invention, the temperature of the hot air may be controlled to 80°C to 250°C based on the temperature of the inlet of the reactor (at the time of introduction) in order to form a granular structure with a high content of the electrode binder on the surface. According to one embodiment of the present invention, the temperature may be controlled to preferably 175°C to 220°C, more preferably 180°C to 220°C, taking into consideration the gradient of the binder content and the aspect ratio of the granules. In the spray drying method, the method of inhaling the hot air is not particularly limited, and examples thereof include a method in which the hot air and the spray direction flow sideways in parallel, a method in which the hot air is sprayed from the top of the drying tower and falls together with the hot air, a method in which the sprayed droplets and the hot air come into countercurrent contact, and a method in which the sprayed droplets flow sideways with the initial hot air and then fall by gravity to come into countercurrent contact. Meanwhile, in one embodiment of the present invention, the outlet temperature of the reactor (the temperature of the hot air discharged from the reactor) during the spray drying may be controlled to 90°C to 130°C.
[0118] If the outlet temperature and / or ΔT, which is the difference between the inlet temperature and the outlet temperature, is low, the drying is not sufficient, particles with a lot of residual solvent are formed, and uniform spherical particles are not produced, and the granules may aggregate or be formed in an irregular state. On the other hand, if the inlet temperature is too high and ΔT is large, the granules are not granulated due to overdrying, and particles with a very small particle size D50 and a low aspect ratio may be produced. Therefore, in order to achieve high sphericity, little binder aggregation, and control the particle size to an appropriate level, it is necessary to control the inlet temperature and outlet temperature within an appropriate range.
[0119] Optionally, the product obtained by spray drying, i.e., the granules, may be heat-treated to harden the surface thereof. In this case, the heat-treatment temperature may be generally 80°C to 300°C.
[0120] According to one embodiment of the present invention, the electrode may be manufactured by a method including the steps of dispersing a plurality of granules on a current collector and compressing the dispersed granules to form an electrode active material layer.
[0121] The electrode active material layer may be formed in the following manner. The current collector is provided with the above-described primer layer, i.e., a primer layer containing a binder and a conductive material, on at least one surface thereof, and then the granules prepared by the above-described method are spread on the current collector with the primer layer.
[0122] According to one embodiment of the present invention, the prepared granules can be fed to a roll-type pressure molding device by a feeder such as a screw feeder to form an electrode active material layer. When forming the electrode active material layer, a current collector having a primer layer formed on at least one surface, entirely or partially, can be fed to the roll of the pressure molding device at the same time as the granules are fed, so that the electrode active material layer can be directly laminated on the current collector. Alternatively, the granules can be spread on the current collector, and the thickness can be adjusted to a uniform level by a blade or the like, and then the electrode active material layer can be formed by molding with a pressure device.
[0123] In the above method, the temperature during roll pressure molding is usually 0 to 200° C., and is preferably higher than the melting point or glass transition temperature of the electrode binder, and more preferably 20° C. or higher than the melting point or glass transition temperature. The molding speed in roll pressure molding can be, for example, 0.1 m / min to 20 m / min, or 1 m / min to 10 m / min. The linear pressure of the press between the rolls can be, for example, 0.2 kN / cm to 30 kN / cm, or 0.5 kN / cm to 10 kN / cm.
[0124] In order to eliminate the variation in thickness of the formed electrode and increase the density of the electrode active material layer to increase the capacity, a pressurization process may be performed as necessary. The post-pressurization method is generally a press process using rolls. In the roll press process, two cylindrical rolls are set up parallel to each other with a narrow gap between them and rotated in opposite directions to sandwich the electrode between them and pressurize it. The temperature of the rolls may be adjustable by heating or cooling, for example.
[0125] According to one embodiment of the present invention, the electrode active material layer may be composed of a single layer formed by the above-mentioned method.
[0126] According to another embodiment of the present invention, the electrode active material layer may be a laminate in which two or more unit active material layers are laminated by repeating the above-mentioned method two or more times, with the electrode layer formed by the above-mentioned method being used as a unit active material layer. When the electrode active material layer includes two or more unit active material layers, after forming one unit active material layer on a current collector by the above-mentioned method, in a post-process, granules may be scattered on the surface of the lower unit active material layer in place of the current collector to form a multi-layer structure.
[0127] According to another aspect of the present invention, there is provided an electrochemical device in which an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode is housed in a battery case together with a lithium-containing nonaqueous electrolyte, and at least one of the positive electrode and the negative electrode is the above-mentioned electrode.
[0128] According to yet another aspect of the present invention, there can be provided an energy storage device including the above-described electrochemical device as a unit cell.
[0129] The separator may be a conventional porous polymer film used in the prior art, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in combination. Also, a thin insulating membrane having high ion permeability and mechanical strength may be used. The separator may include a safety reinforced separator (SRS) in which a ceramic material is thinly coated on the surface of the separator. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, polyethylene terephthalate fiber, or the like, may be used, but is not limited thereto.
[0130] The electrolytic solution contains a lithium salt as an electrolyte and an organic solvent for dissolving the lithium salt. The lithium salt can be used without any limitation as long as it is one that is commonly used in electrolytes for electrochemical elements. For example, the anion of the lithium salt is F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C- , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , (CF3CF2SO2)2N - Or two or more of these may be used.
[0131] The organic solvent contained in the electrolytic solution may be any commonly used organic solvent without any limitation. Representative examples include propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfide, tetrahydrofuran, or two or more of these.
[0132] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used since they are high-viscosity organic solvents with high dielectric constants and can easily dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed with chain carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte solution having high electrical conductivity can be prepared, which can be more preferably used.
[0133] Optionally, the electrolyte stored according to the present invention may further contain additives such as overcharge inhibitors that are typically included in electrolytes.
[0134] In an electrochemical device according to an embodiment of the present invention, a separator is disposed between a positive electrode and a negative electrode to form an electrode assembly, and the electrode assembly is placed in, for example, a pouch, a cylindrical battery case, or a prismatic battery case, and an electrolyte is injected to complete the electrochemical device. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and the resulting product may be placed in a battery case and sealed to complete the electrochemical device.
[0135] Here, the specific structures of the electrochemical device and the energy storage device are the same as those conventionally known, and therefore, description thereof will be omitted in this specification.
[0136] The present invention will be described below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those having ordinary skill in the art.
[0137] [Electrode manufacturing] Example 1 Preparation of primer layer on current collector Carbon black (specific surface area 58 m2) is used as a conductive material. 2 A slurry for the primer layer was prepared by mixing 100% ethylenediaminetetraacetate (0.1 wt. / g, primary particle size 37 nm) with styrene butadiene rubber (SBR) as a binder and carboxymethyl cellulose (CMC daicel2200 1.5% aqueous solution) as a dispersant in water as a dispersion medium. At this time, the content ratio of the conductive material, binder and dispersant in the slurry was the same as the content ratio of the conductive material, binder and dispersant in the primer layer to be formed later, and the content ratio is shown in Table 1 below. The solid content of the slurry for the primer layer was 7 wt.%.
[0138] The prepared primer layer slurry was applied to one surface of a copper current collector (thickness: 10 μm) and dried at 130° C. to form a primer layer on the entire surface of the copper current collector. The thickness of the primer layer, the type of binder and the glass transition temperature Tg are also shown in Table 1 below.
[0139] Preparation of granules for electrode active material layer As electrode active materials, 1.91 parts by weight of natural graphite with a sphericity of 0.95 and 76.5 parts by weight of artificial graphite with an average sphericity of 0.9, carbon black (Super C65) as electrode conductive material, carboxymethylcellulose (daicel 2200, aqueous solution form, solid content concentration 1.5 wt%) as electrode dispersant, and modified styrene butadiene copolymer (Grade Name AX-B119) as electrode binder were mixed with water as a dispersion medium in a weight ratio of 95.6:1.0:1.1:2.3 to prepare a slurry with a viscosity of about 1,000 cPs using a homogenizer. At this time, the solid content of the slurry was 30 wt%. In the above weight ratio, carboxymethylcellulose was calculated based on the solid content.
[0140] The prepared slurry was dried by feeding it into a spray dryer together with hot air under pressure conditions of -40 mmH2O. The conditions of the spray dryer were controlled as follows: inlet temperature 180°C, outlet temperature 90°C, and rotation speed 18,000 rpm. The obtained granules were sieved to remove coarse powder of 150 μm or more, and fine powder of less than 40 μm was further separated. The separated fine powder was mixed with the granules from which only the coarse powder was removed, to finally prepare granules for electrodes containing a larger amount of fine powder than the previous granules. The granules had a center portion containing a plurality of electrode active materials and electrode conductive materials, and a surface portion located outside the center portion and containing an electrode binder binding the electrode active materials and electrode conductive materials. The obtained granules had an average particle size D50 of 66.5 μm and an aspect ratio of 0.96. FIG. 3 shows an SEM image of the granule particles prepared above.
[0141] Electrode fabrication The current collector having the primer layer is then heated to a thickness of 25 cm using a thickness adjusting bar. 2The granules prepared as described above were uniformly spread in an amount of 400 mg per sheet, and pressed at a speed of 2 m / min under conditions of 0.7 ton / cm and 60°C using a roll-to-roll hot rolling molding machine, which is a sheeting machine, to form an electrode active material layer, thereby manufacturing an electrode.
[0142] Examples 2 to 10 A current collector having a primer layer and a negative electrode including the same were manufactured in the same manner as in Example 1, except that the content ratio of the conductive material, the binder, and the dispersant, the type of the binder, and the thickness of the primer layer were changed to the conditions shown in Table 1 below.
[0143] [Adhesive strength evaluation] The negative electrodes prepared in Examples 1 to 10 were prepared with the same porosity, cut to a width of 20 mm and a length of 15 cm, and attached to a glass plate using 3M double-sided tape. The double-sided tape used was a commonly used product, with adhesive strength of both sides of 200 to 1,000 gf x 20 mm, and a width of 20 mm or more that could cover the entire area of the negative electrode.
[0144] The negative electrode was attached to the double-sided tape attached to the glass plate, and then the double-sided tape was thoroughly adhered to the negative electrode by rolling it back and forth 10 times using a 2 kg roller. The adhesive strength of this sample was measured using a tensile strength tester in peel test mode at a 90° angle, and the measurement results are shown in Table 1 below.
[0145] [Table 1]
[0146] Meanwhile, Fig. 2a is a SEM image of the cross section of the electrode before rolling in Example 1, and Fig. 2b is a SEM image of the cross section of the electrode before rolling in Example 2. Although there is no difference in the appearance between Example 1 and Example 2, there was a difference in adhesion strength as shown in the results in Table 1. This difference in adhesion strength is due to a problem in the binding strength between the primer layer and the electrode active material layer, and as can be seen from Figs. 2a and 2b, referring to the SEM images of the cross section of the non-rolled electrode, localized peeling between the primer and the electrode active material layer was observed in Example 1 (Fig. 2a), while no localized peeling was observed in Example 2 (Fig. 2b). From this, it was confirmed that Example 2, which does not contain any dispersant, has a superior effect in terms of adhesion strength.
[0147] [Evaluation of changes over time] After the preparation of Examples 9 and 10, the adhesive strength of the adhesive was evaluated over time by leaving the adhesive for 4 days at room temperature and high humidity (relative humidity 65% or more). The results are shown in Table 2 below.
[0148] [Table 2]
[0149] As can be seen from the results in Table 2, after being left for 4 days, Examples 9 and 10 did not show any significant decrease in adhesive strength due to aging.
[0150] [Confirmation of binder distribution in granules] The cross section of the granules prepared in Example 1 was analyzed by radial profile analysis using EPMA (JXA-8350F, -15 kV, 20 nA stage mapping conditions) to confirm the binder distribution in the granules.
[0151] First, the binder of the granules obtained in Example 1 was dyed using OsO4. The dyeing was carried out by placing the granules in each glass container using an OsO4 aqueous solution, and then evaporating the reagent to react. Then, the granules were mixed with epoxy resin, fixed to a silicon mold, and hardened to obtain a granule matrix. Next, a cross-sectional sample was prepared from the granule matrix using an ion milling device (Hitachi IM5000, acceleration voltage: 6 kV). The prepared cross-sectional sample was fixed in an EPMA device, the granules were positioned at the center of the display, and the cross-section was scanned using a stage mapping method, and a mass map was created using the scan results, from which an Os map was extracted.
[0152] From the extracted Os map, the distribution of the binder in the granules of Example 1 was confirmed. Specifically, it was confirmed that the granules obtained in Example 1 have a higher binder content in the surface region up to 70% or more, particularly 80% or more of the radius of the granule surface, than in the central region.
[0153] The present invention has been described above with reference to the embodiments and drawings. However, a person having ordinary knowledge in the field to which the present invention belongs will be able to make various applications and modifications within the scope of the present invention based on the above content. [Explanation of symbols]
[0154] 101 Center 102 Surface part
Claims
1. A current collector; a primer layer formed on the entirety or a part of at least one surface of the current collector; an electrode active material layer located on a current collector having the primer layer, the electrode active material layer includes an electrode active material and an electrode binder, the electrode active material includes a plurality of granules bound by the electrode binder, the primer layer comprises a binder and a conductive material, 13. An electrode, comprising: a binder and a conductive material each having a total weight of 90% or more of the binder and conductive material, based on the total weight of the primer layer.
2. 2. The electrode according to claim 1, wherein the sum of the content of the binder and the conductive material is 94% by weight or more based on the total weight of the primer layer.
3. The electrode of claim 1 , wherein the primer layer is dispersant-free.
4. The electrode according to claim 1 , wherein the primer layer further comprises a dispersant, and the content of the dispersant is 6 wt % or less based on the total weight of the primer layer.
5. The electrode according to claim 4 , wherein the dispersant is a cellulose-based polymer, an emulsifying surfactant, or two or more of them.
6. 2. The electrode according to claim 1, characterized in that the binder has a glass transition temperature Tg of -40°C to 45°C.
7. The binder may be styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), styrene butadiene styrene block polymer (SBS), styrene ethylene butadiene block polymer (SEB), styrene-(styrene butadiene)-styrene block polymer, natural rubber (NR), isoprene rubber (IR), ethylene-propylene-diene terpolymer (EPDM), poly(ethylene-co-propylene-co-5-methylene-2-norbornene), polytetrafluoroethylene (PTFE), polyvinylidene fluoride, ...
2. The electrode according to claim 1, characterized in that it contains polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, polyethylene oxide, polypropylene oxide, polyarylate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, or two or more of these.
8. 2. The electrode of claim 1, wherein the electrode active material layer comprises an electrode active material, an electrode conductive material, and an electrode binder, the electrode active material and the electrode conductive material comprising a plurality of granules bound together by the electrode binder.
9. The electrode conductive material is 10 m 2 / g~1,400m 2 9. The electrode according to claim 8, characterized in that it has a specific surface area of 1000 nm / g.
10. 2. The electrode according to claim 1, wherein the thickness of the primer layer is from 300 nm to 1.5 μm.
11. 2. The electrode according to claim 1, wherein the granules contained in the electrode active material layer are produced by a method including the steps of: mixing an electrode active material and an electrode binder with a dispersion medium to prepare a slurry; and spray-drying the slurry.
12. The electrode of claim 11 , wherein the slurry further comprises an electrode conductive material.
13. 2. The electrode according to claim 1, wherein the electrode is a dry electrode manufactured by a method including the steps of: dispersing a plurality of granules on a current collector; and rolling the dispersed plurality of granules to form an electrode active material layer.
14. An electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode is housed in a battery case together with a lithium-containing non-aqueous electrolyte, An electrochemical element, wherein at least one of the positive electrode and the negative electrode is the electrode according to claim 1 .
Citation Information
Patent Citations
Electrode and non-aqueous secondary battery
JP2008077993A
Acetylene black, method for producing the same and use thereof
JP2009035598A
Negative electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2014229581A
Method for manufacturing lithium ion secondary battery electrode
JP2016100127A
Electrode for electrochemical-element, and electrochemical element
WO2011013756A1